Cultivation of Social Attitudes in Social Studies Subjects for Sixth Grade of Elementary School - Wangi, Hayu Eka; Supriyanto, Teguh; Trimurtini (MIMBAR PGSD Undiksha, 2024)
There are still some students who have low social attitudes. This shows that students are still less sensitive to friends, do not care about their surroundings, do not trust classmates, have difficulty adjusting to new relationships, want to win alone when playing, and often fight when playing. This study aims to evaluate the instillation of social attitudes in students who take social studies lessons. Supporting informants for this study were teachers and grade VI students. This study uses a qualitative method with a case study approach. The research data were collected through observation, interviews, questionnaires and documentation. Analysis of research data begins with data reduction, data presentation, and conclusions. The validity of the data is checked using technical triangulation and source triangulation. Indicators to be studied in students' social attitudes include honesty, discipline, helping each other, tolerance and politeness. The results of the study show that students' social attitudes, especially those related to tolerance and helping each other have been well ingrained since observation and interviews. directions, reprimands, sanctions, and providing good examples to their students. This study has implications for the process of implementing the instillation of social attitudes in grade VI students, in the world of education students are not only given knowledge and science to become intelligent people, but students are also given provisions to have skills and be able to shape student behavior in accordance with applicable norms and values. The development of these social attitudes can be a provision for students in facing the challenges and social conditions that they will face later.